Evaluation of Football Achievement Coaching Program at Academy Terang Bangsa Semarang - Ardana, Alvito Wahyu; Junaidi, Said (Java Mutiara Media, 2025)
This research aims to evaluate the football achievement coaching program case study at Terang Bangsa Academy Semarang using the CIPP (Contexs, Input, Process, Product) evaluation model. This research is a qualitative descriptive research. The research location was at Terang Bangsa Academy, with data collection using observation, interview, and documentation methods. This research was conducted from April 24, 2024 to April 27, 2024 at the Terang Bangsa Academy training ground. The main data sources include athletes, coaches, and academy administrators. The data analysis technique used is data triangulation. The results showed that in terms of contexs, the organizational structure is running well. However, in terms of input, there are still shortcomings due to funding issues which are the main obstacle, where the academy depends on the Terang Bangsa foundation and donations from the church. In terms of process, the training program is running well with the implementation of an adapted Dutch football curriculum. Overall, in terms of product, the achievements have been good, as seen from the existing documentation. Suggestions on this research need to look for additional sources of funding apart from church and foundation donations, such as partnering with local governments or companies, to ensure the sustainability and development of the facility.